Benchmarking and effects of reforms in the fixed telecommunications industry: A DDF approach. Issue 2 (March 2015) - Bruno, Clementina; Manello, Alessandro
Abstract: Our article proposes an application of the Directional Distance Function (DDF) approach to the fixed telecommunication field. In particular, we present an efficiency evaluation of European fixed telecom operators, where the DDF tool allows for asymmetric treatment of outputs characterized by a different degree of desirability: broadband lines (a market still in expansion, related to a welfare-improving service) and narrow band lines (an almost saturated market, corresponding to a "minimal" TLC service in developed countries). Finally, by means of a second stage regression, we investigate the effect on technical efficiency of set of variables representing the competitive environment, the ownership structure and the degree of vertical separation. Our results show that the assumptions embedded in the DDF model influence relevantly the technical efficiency estimates, where important potential bias can arise if the duality of outputs is ignored, with a subsequent relevant impact also on the second stage results. These findings highlight the relevance of choosing benchmarking models consistent with the features of the analysed technology and show that the DDF approach is a flexible tool able to accommodate even complex output structures. Highlights: This work proposes an application of the DDF approach to the fixed TLC field. DDF allows for asymmetric treatment of differently desirable outputs. DDF assumptions influence the efficiency estimates and the second stage results. DDF is a flexible tool allowing benchmarking even with complex output structures.